2007
DOI: 10.1111/j.1439-0418.2007.01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation of pre‐ovipositional period in the brown planthopper, Nilaparvata lugens, collected in tropical, subtropical and temperate Asia

Abstract: We investigated the pre-ovipositional period of Nilaparvata lugens originating from tropical, subtropical and temperate regions of East and Southeast Asia using laboratory experiments to compare the migration capability of the populations. Macropter females collected in 1992 from Japan and subtropical North Vietnam had a longer immature period than those from tropical Indochina Peninsula, i.e. the day of the first oviposition after eclosion was about 3 days later in the former populations. Populations collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Using exactly the same populations (same original collections), Wada et al (2007) confirmed that all subtropical and temperate populations had longer pre-ovipositional periods than the tropical populations. Using exactly the same populations (same original collections), Wada et al (2007) confirmed that all subtropical and temperate populations had longer pre-ovipositional periods than the tropical populations.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Using exactly the same populations (same original collections), Wada et al (2007) confirmed that all subtropical and temperate populations had longer pre-ovipositional periods than the tropical populations. Using exactly the same populations (same original collections), Wada et al (2007) confirmed that all subtropical and temperate populations had longer pre-ovipositional periods than the tropical populations.…”
Section: Discussionmentioning
confidence: 56%
“…The biotype composition of the N. lugens populations (proportions of individuals showing virulence on different rice cultivars) in Japan, China, and northern Vietnam are similar, and show a clear discordance from those of tropical populations Wada et al, 1994;Tanaka & Matsumura, 2000). In addition, Wada et al (2007) demonstrated that macropter females originating from temperate and subtropical East Asia had a longer pre-ovipositional period than those of tropical populations. In addition, Wada et al (2007) demonstrated that macropter females originating from temperate and subtropical East Asia had a longer pre-ovipositional period than those of tropical populations.…”
Section: Introductionmentioning
confidence: 89%
“…This was explained by the difference in the sources of immigrants, i.e., Japanese N. lugens were originated from South China in most cases, but sometimes also from other tropical countries. Wada et al (2007) demonstrated that N. lugens populations collected from subtropical and temperate East Asia (Northern Vietnam, Central China, and Kyushu, Japan) had longer adult immature stage before oviposition, compared to tropical populations (Southern Vietnam, Thailand, and Malaysia). The periods required for 50 % female to begin oviposition at 25 °C were 4.7 days for tropical populations and 7.6 days for East Asian populations ( Fig.…”
Section: Natural Enemy Abundancementioning
confidence: 97%
“…For migratory macropters, the preoviposition period was difficult to estimate because it can be prolonged to 1 month or longer when there is no appropriate habitat available (Kisimoto & Sogawa, 1995). In addition, macropterous BPH originating from temperate and subtropical East Asia had a longer pre-oviposition period than those of tropical populations (Wada et al, 2007). The pre-oviposition period of BPH was influenced by food quality and probably by nymphal rearing densities and resistant rice varieties (Lu et al, 2004;Wada et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, macropterous BPH originating from temperate and subtropical East Asia had a longer pre-oviposition period than those of tropical populations (Wada et al, 2007). The pre-oviposition period of BPH was influenced by food quality and probably by nymphal rearing densities and resistant rice varieties (Lu et al, 2004;Wada et al, 2007). In this study, we evaluated whether BPH was in the pre-oviposition period in rice fields through determining the levels of Vg ⁄ Vt.…”
Section: Discussionmentioning
confidence: 99%